2020
DOI: 10.7150/thno.47913
|View full text |Cite
|
Sign up to set email alerts
|

LPA3-mediated lysophosphatidic acid signaling promotes postnatal heart regeneration in mice

Abstract: Background: Lysophosphatidic acid (LPA) is a small glycerophospholipid that acts as a potent extracellular signal in various biological processes and diseases. Our previous work demonstrated that the expression of the LPA receptors LPA 1 and LPA 3 is elevated in the early postnatal heart. However, the role of this stage-specific expression of LPA 1 and LPA 3 in the heart is unknown. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“… 24 , 25 , 26 , 27 , 28 , 29 Studies have shown that myocardial‐specific overexpression of the small glycerol phospholipid hemolytic phosphatidic acid (LPA) can improve myocardial function and promote heart regeneration after MI. 30 We also observed that LPA was elevated after Pycr1 KO, which may also be one of the ways in which loss of Pycr1 exerts a protective effect. In addition, we observed elevated levels of bile acids in Pycr1 KO mice.…”
Section: Discussionsupporting
confidence: 55%
“… 24 , 25 , 26 , 27 , 28 , 29 Studies have shown that myocardial‐specific overexpression of the small glycerol phospholipid hemolytic phosphatidic acid (LPA) can improve myocardial function and promote heart regeneration after MI. 30 We also observed that LPA was elevated after Pycr1 KO, which may also be one of the ways in which loss of Pycr1 exerts a protective effect. In addition, we observed elevated levels of bile acids in Pycr1 KO mice.…”
Section: Discussionsupporting
confidence: 55%
“…LPA can exert a wide range of biological effects by binding to the LPA receptors (LPA 1-6 ) and signal through numerous effector pathways activated by heterotrimeric G proteins, including G i/o , G 12/13 , G q , and G s ( 44 ). Disturbances in normal LPA signaling may contribute to a range of diseases, including neuropsychiatric disorders, asthma, acute lung injury, fibrosis, and cardiovascular disease ( 36 38 , 45 47 ). LPA 3 couples to G αi/o and G αq/11 and mediates LPA-induced Ca 2+ mobilization, inhibition and activation of adenylate cyclase, activation of PLC, and activation of MAPK ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidic acid (LPA) is a bioactive lipid mediator of inflammation via lysophosphatidic acid receptors 1–6 (LPA 1 –LPA 6 ), contributing to the pathogenesis of many diseases including asthma, acute lung injury, fibrosis, and postnatal heart regeneration ( 36 38 ). A study reported LPA 1 knockout reduces LPS-induced inflammatory cytokine signaling in the lungs ( 39 ), and inflammatory cytokines are effective inducers of NETs.…”
Section: Introductionmentioning
confidence: 99%
“…The stroma signals to CMs thus playing a crucial role in their proliferation. Lysophosphatidic acid (LPA) acts as a potent extracellular signal in various biological processes and diseases and LPA3-mediated LPA signaling was shown to play a pivotal role in CMs proliferation (Wang et al, 2020a). The component of extracellular matrix was shown to affect the growth and differentiation of CMs in mice, mediated by agrin (Bassat et al, 2017) and myeloid-derived growth factor (Wang et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%